Antimicrobial and antioxidant potential of methanolic extracts from different parts of Stevia rebaudiana Bertoni cultivated in Bulgaria - Dinev, Toncho; Tzanova, Milena; Rusenova, Nikolina; Grozeva, Neli; Gerdzhikova, Mariya; Beev, Georgi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Stevia rebaudiana Bertoni is a plant species, which is frequently used not only as a sweetener, but also for its antibacterial and antioxidant properties. Nowadays, there are a large number of studies on the antimicrobial and antioxidant activity of S. rebaudiana leaves, but there are almost no data about the antimicrobial and antioxidant potential of extracts from the other parts of S. rebaudiana. The aim of the present study is to provide data of the antibacterial and antioxidant potential of methanolic extracts from different parts of S. rebaudiana (flowers, leaves, stems, rhizomes, and tubers) cultivated in Bulgaria. Antibacterial activity of the extracts against Staphylococcus aureus, Bacillus cereus and Escherichia coli was evaluated by agar well diffusion method, rutin content - by HPLC method, total phenolic content and radical scavenging potential - by UV-Vis analysis. S. rebaudiana extracts demonstrated antibacterial activity mainly against S. aureus - flower extracts expressed the highest activity, followed by the leaf and stem extracts. Only flower and leaf extracts demonstrated very low antibacterial activity against B. cereus. S. rebaudiana extracts did not show any antibacterial activity against E. coli. Methanolic extracts of this plant are rich in antioxidants. The highest concentrations of rutin and total phenols were found in the rhizomes of the plants, followed by the leaves, tubers, flowers, and stems, which corresponded to the radical scavenging potential of the same plant part. Comparisons between Trolox equivalents and gallic acid equivalents in different parts of S. rebaudiana on one hand, and Trolox equivalents and rutin concentration on the other hand showed a positive dependence and high values of the Pearson correlation - 0.9612 and 0.9707, respectively. The most important part of S. rebaudiana with medicinal significance (the leaves) has both comparatively good antibacterial activity and high antioxidant content, although the flowers and rhizomes expressed higher antibacterial and antioxidant activity, respectively. The experimental results imply that the cultivation area and climatic conditions of Bulgaria are very suitable for cultivation of S. rebaudiana plants with high content of antioxidants.